Copper terminal electrode slurry and preparation method and application thereof

By preferring the combination of glass powder and organic binder, the problem of insufficient density of copper-end electrode slurry at low temperature sintering is solved, and the connection quality of the inner and outer electrodes and the high-temperature insulation performance of ceramic capacitors are improved, which is suitable for the production of high-end ceramic capacitors.

CN116844755BActive Publication Date: 2024-12-27GUANGDONG FENGHUA ADVANCED TECHNOLOGY (HOLDING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310936449.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2024-12-27
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

The existing copper end electrode slurry is insufficient in compactness during low-temperature sintering, resulting in poor connection between the inner and outer electrodes of ceramic capacitors, affecting the reliability of the product and high-temperature insulation performance.

Method used

Using a combination of 65% to 70% copper powder, 8% to 15% glass powder and 17% to 27% organic binder, the glass powder component and copper powder particle size are preferred, and SiO2, B2O3, GeO2, etc. Components, promote crystallization and improve acid resistance, and use uncoated copper powder and specific organic binders to ensure the density and connection quality of low-temperature sintering.

Benefits of technology

It realizes that ceramic capacitors have excellent density and high-temperature insulation properties after low-temperature sintering, reduces the internal stress of the product, and improves the overall performance of the capacitor, especially its applicability in X7R capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116844755B_ABST
    Figure CN116844755B_ABST
Patent Text Reader

Abstract

The present invention relates to a copper terminal electrode slurry and a preparation method and application thereof, belonging to the technical field of electronic components. The copper terminal electrode slurry provided by the present invention comprises the following components by mass percentage: 65% to 70% copper powder, 8% to 15% glass powder, and 17% to 27% organic binder; the glass powder is composed of BaO, B2O3, ZnO, Al2O3, CaO, SiO2, GeO2, SrO, TiO2, K2O, Li2O, and La2O3. The electrode slurry of the present invention can also have excellent compactness when sintered at low temperature and the internal and external electrodes are well connected, thus overcoming the defect of low temperature sintering of capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic components, and in particular relates to a copper terminal electrode slurry and a preparation method and application thereof. Background Art

[0002] The introduction of 5G mobile communication systems in 2020 and the electronicization of automobiles due to the use of advanced driver assistance systems (ADAS) have led to an increase in the number of electronic components installed year by year, and the number of multilayer ceramic capacitors (MLCCs) installed has also continued to increase. Therefore, the demand for capacitors is expected to increase in the future.

[0003] MLCC is divided into Class I capacitors and Class II capacitors according to the different ceramic dielectric materials used. The main components of the ceramic dielectric of Class I NPO characteristic capacitors are zirconium, strontium, and calcium. The main components of the ceramic dielectric of Class II X7R and Y5V characteristic capacitors are barium and titanium. Due to the different main components of ceramics, it is necessary to design corresponding different terminal slurry bases to obtain better matching and achieve better product performance.

[0004] At present, the existing domestic copper terminal electrode slurry products generally need to be sintered at 850℃-930℃, and imported copper paste needs to be sintered at 780℃-790℃, but the density still does not meet the requirements of high-end product lines. The high-end market requires ceramic capacitors to have higher end density, smaller product internal stress, more stable high-temperature insulation performance and other properties. Therefore, it is very important to develop ceramic capacitors and electrode slurries that meet the requirements of high-end products.

[0005] In order to achieve higher performance requirements of capacitors, the internal stress of capacitors must be controlled in a lower range, so the copper terminal electrodes of capacitors need to be sintered at a lower temperature. However, sintering at a lower temperature will not make the electrodes denser, causing the nickel layer to penetrate during product electroplating, and gaps are likely to form at the connection between the inner and outer electrodes, causing other reliability performance to deteriorate. Therefore, it is urgent to develop copper terminal electrode slurry that can meet the performance requirements of capacitors even when sintered at low temperatures. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a copper terminal electrode slurry and a preparation method and application thereof.

[0007] The present invention is achieved through the following technical solutions:

[0008] The invention provides a copper terminal electrode slurry, which comprises the following components by mass percentage: 65% to 70% of copper powder, 8% to 15% of glass powder, and 17% to 27% of organic binder; the glass powder is composed of the following components by mass percentage: 20% to 35% of BaO, 15% to 22% of B2O3, 20% to 30% of ZnO, 7% to 13% of Al2O3, 6% to 10% of CaO, 6% to 12% of SiO2, 1% to 5% of GeO2, 0.05% to 0.3% of SrO, 0.05% to 0.5% of TiO2, 0.05% to 0.3% of K2O, 1% to 5% of Li2O, and 1% to 5% of La2O3.

[0009] The copper terminal electrode slurry of the present invention has excellent compactness and good connection between internal and external electrodes even when sintered at low temperature by selecting the glass powder component, thus overcoming the defects caused by low temperature sintering of capacitor terminal electrodes. The electrode slurry of the present invention uses SiO2, B2O3, and GeO2 as glass formers, Al2O3, ZnO, TiO2, and La2O3 as glass intermediates to promote crystallization and improve acid resistance; BaO, CaO, SrO, K2O, and Li2O as glass modifiers to increase glass viscosity and inhibit crystallization, low melting point, and reactivity with chip porcelain, so that the electrode slurry has good low temperature sintering performance.

[0010] As a preferred embodiment of the copper terminal electrode slurry of the present invention, the particle size of the copper powder is 0.5 μm to 3.0 μm. Copper powder in this particle size range can make the slurry have good density after sintering.

[0011] Preferably, the copper powder is uncoated copper powder. The copper powder used in the present invention can be prepared by atomization or chemical method, but must be uncoated. Coated copper powder will affect the density of sintering, thereby affecting the performance of the capacitor.

[0012] As a preferred embodiment of the copper terminal electrode slurry described in the present invention, the organic binder includes an organic solvent, an organic resin and an organic additive; the organic solvent is at least one of alcohols, esters, aromatic hydrocarbons and ether solvents; the organic resin is a polymer of acrylic resin and PVB resin and / or a polymer of acrylic resin and ethyl cellulose; the organic additive includes at least one of a dispersant, a leveling agent, a defoaming agent and a stabilizer.

[0013] Preferably, in terms of mass percentage, the organic binder includes 18%-58% of organic resin, 24%-81.5% of organic solvent, and 0.5%-18% of organic additive.

[0014] Preferably, the alcohol includes at least one of terpineol, isooctyl alcohol and benzyl alcohol.

[0015] Preferably, the esters include at least one of diethylene glycol butyl ether acetate and diethylene glycol ethyl ether acetate.

[0016] Preferably, the aromatic hydrocarbons include at least one of ethylene glycol ether and ethyl acetate.

[0017] Preferably, the ethers include at least one of diethylene glycol butyl ether and diethylene glycol ethyl ether.

[0018] The present invention also provides a method for preparing the copper-terminated electrode slurry, comprising the following steps: uniformly mixing the copper powder, glass powder and organic binder, and grinding to a fineness of ≤6.0 μm to obtain the copper-terminated electrode slurry.

[0019] The preparation method of the copper terminal electrode slurry of the present invention is simple, the fineness is controlled to be ≤6.0 μm, the compactness of the sintered rear end electrode can be ensured, and the sintered rear end electrode can be applied to industrial production.

[0020] Preferably, the uniform mixing method is planetary dispersing, mixing, and mixing by a mixer, and the stirring time is 5 hours to 6 hours; the grinding is grinding and dispersing by a three-roll mill or a horizontal sand mill.

[0021] As a preferred embodiment of the method for preparing the copper terminal electrode slurry of the present invention, at least one of the following conditions is met:

[0022] (1) The preparation method of the organic binder is as follows: fully dissolving an organic auxiliary agent and an organic resin in an organic solvent at 80° C. to 95° C.;

[0023] (2) The preparation method of the glass powder is as follows: the components of the glass powder are mixed uniformly by ball milling, melted at 1300° C. to 1400° C., quenched, and crushed to an average particle size of 2 μm to 3 μm, and sieved to obtain the glass powder.

[0024] Preferably, in the preparation method of the glass powder, the melting is carried out in a high-temperature frit furnace, and the glass powder composition is precisely controlled by top loading and bottom flow. Screening can remove coarse particles and play a dispersing role.

[0025] Another object of the present invention is to provide an application of the copper terminal electrode slurry in a ceramic capacitor.

[0026] The copper terminal electrode slurry of the present invention can be widely used in chip multilayer ceramic capacitors, especially Class II ceramic capacitors, and in particular in X7R capacitors. It has a higher adaptability and can overcome the defects caused by low-temperature sintering of the terminal electrodes of X7R capacitors, thereby improving the performance of X7R capacitors.

[0027] Another object of the present invention is to provide a method for preparing a ceramic capacitor, including slurry mixing, making a dielectric diaphragm, alternately overprinting internal electrodes and dielectric layers, lamination, cutting, debinding, sintering, capping electrodes, sintering ends, nickel plating and tin plating. The sintering end method is: coating the copper end electrode slurry on both ends of the ceramic core of the ceramic capacitor, drying, and sintering in an inactive gas; the sintering includes sintering in a low temperature zone and sintering in a high temperature zone, and the inactive gas sintered in the low temperature zone is humidified. The inactive gas humidification method is: passing the inactive gas through water before sintering.

[0028] The present invention has found through research that sintering the copper terminal electrode slurry of the present invention in combination with a humidified inactive gas can make the capacitor more compact, the internal and external electrodes well connected, the stress near the copper slurry end smaller, and the high-temperature insulation performance more stable.

[0029] The inactive gas described in the present invention is an inert gas or nitrogen. In the embodiment of the present invention, nitrogen is used as the reaction atmosphere.

[0030] As a preferred embodiment of the method for preparing the ceramic capacitor of the present invention, the low temperature zone sintering is to maintain a constant temperature at 460°C to 470°C for at least 7 minutes, and the high temperature zone sintering is to maintain a constant temperature at 740°C to 770°C for 5 minutes to 10 minutes.

[0031] In the preparation method of the ceramic capacitor of the present invention, the low temperature zone is kept at a constant temperature for at least 7 minutes, which is conducive to the discharge and decomposition of the organic solvent components in the slurry. The slurry of the present invention also has good density when sintered at low temperature, and the terminal electrode is well connected with the internal electrode.

[0032] As a preferred embodiment of the method for preparing the ceramic capacitor of the present invention, the oxygen content in the inert gas sintered in the low temperature zone is 0 to 200 ppm.

[0033] Another object of the present invention is to provide a ceramic capacitor made by the method for making the ceramic capacitor.

[0034] The ceramic capacitor obtained by sealing with the copper-terminal electrode slurry of the present invention has a lower sintering temperature, better terminal density, smaller product internal stress, and more stable high-temperature insulation performance, which effectively improves the product quality of the ceramic capacitor.

[0035] The present invention has the following beneficial effects: the copper-terminal electrode slurry of the present invention has excellent sintering performance at low temperature by optimizing the glass powder component and rationally compounding with copper powder and adhesive, and has good compactness after low-temperature sintering. The ceramic capacitors, especially X7R capacitors, prepared by capping the copper-terminal electrode slurry of the present invention have lower sintering temperature, better terminal compactness, smaller product internal stress, and more stable high-temperature insulation performance, which effectively improves the product quality of ceramic capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The terminal electrode density test results of the ceramic capacitor prepared by the slurry of Example 1 of the present invention are shown in FIG. Figure 1 The left picture is the SEM picture of the slurry after sintering. Figure 1 The right picture is a scanning electron microscope image of the connection between the inner and outer electrodes;

[0037] Figure 2 The terminal electrode density test results of the ceramic capacitor prepared by sintering CX701 slurry without humidified nitrogen in the present invention are shown in FIG. Figure 2 The left picture is the SEM picture of the slurry after sintering. Figure 2 The right picture is a scanning electron microscope image of the connection between the inner and outer electrodes;

[0038] Figure 3 The terminal electrode density test results of the ceramic capacitor prepared by sintering CF63 slurry without humidified nitrogen in the present invention are shown in FIG. Figure 3 The left picture is the SEM picture of the slurry after sintering. Figure 3 The right picture is a scanning electron microscope image of the connection between the inner and outer electrodes;

[0039] Figure 4 The terminal electrode density test results of the ceramic capacitor made by sintering imported slurry without humidified nitrogen in the present invention are shown in FIG. Figure 4 The left picture is the SEM picture of the slurry after sintering. Figure 4 The right picture is a scanning electron microscope image of the connection between the inner and outer electrodes;

[0040] Figure 5 The insulation resistance test results of the ceramic capacitors made of the slurry of Example 1 of the present invention and the ceramic capacitors made of the imported slurry by sintering without humidified nitrogen are shown. DETAILED DESCRIPTION

[0041] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0043] The component contents of the copper terminal electrode slurry of the embodiment and the comparative example and the composition contents of the glass powder in the copper terminal electrode slurry of the embodiment and the comparative example are shown in Table 1. The organic binder in the copper terminal electrode slurry of the embodiment and the comparative example includes 55% of organic solvent, 35% of organic resin and 10% of organic additive; the organic solvent is diethylene glycol butyl ether and pinene alcohol; the organic resin is KFA-1000 of Huying Chemical; and the organic additive is BYK's silicone additive BYK-077.

[0044] The preparation methods of the copper terminal electrode slurries of Examples 1-4 and Comparative Examples 1-10 are as follows:

[0045] Dissolving the organic resin and the organic additive in an organic solvent at 80°C to 95°C in a water bath to obtain an organic adhesive;

[0046] Weigh the components of glass powder according to the percentage content in Table 1, mix and grind with a vibrating ball mill, and then put them into a high-temperature frit furnace for melting. The high-temperature frit furnace adopts the method of top loading and bottom flow, and the temperature is 1300℃~1400℃. After melting, put them into a sheet rolling machine for quenching, and use a jet mill to crush and granulate the product. Grind it to the average particle size requirement of 2~3μm, and sieve and disperse to obtain glass powder;

[0047] Copper powder (particle size of 0.5μm to 3.0μm) and glass powder are added to the organic binder according to the percentage in Table 1, stirred for 5h to 6h by a planetary dispersing, mixing and kneading machine, and evenly dispersed, ground and dispersed by a three-roll mill, and the fineness is controlled at ≤6.0μm to obtain a copper terminal electrode slurry.

[0048] Table 1 Electrode slurry composition and glass powder composition of the embodiment and comparative example (%)

[0049]

[0050]

[0051] The copper-terminal electrode slurry of the embodiment and comparative example and the existing product are used to prepare ceramic capacitors. The preparation method of the ceramic capacitor includes mixing slurry, making dielectric diaphragms, alternately superimposing inner electrodes and dielectric layers, lamination, cutting, debonding, sintering, capping electrodes, sintering ends, nickel plating and tin plating processes. Except for the different sintering end processes, the rest are the same. The sintering end method is: coating the copper-terminal electrode slurry of embodiments 1-4, comparative examples 1-10 and the existing product on both ends of the ceramic core of the ceramic capacitor, drying, and sintering. The sintering atmosphere, sintering temperature, and sintering time are shown in Table 2.

[0052] Table 2 Sintering parameters of ceramic capacitors prepared in Examples and Comparative Examples

[0053]

[0054]

[0055] The ceramic capacitors obtained from the copper-terminal electrode slurries of the embodiments and comparative examples and the electrode slurries of existing products were subjected to performance tests. The test methods and test results of density, deposited nickel permeability, internal stress, and welding resistance thermal insulation resistance are shown in Table 3.

[0056] Table 3 Ceramic capacitor test methods and test results

[0057]

[0058]

[0059] Figure 1 The terminal electrode density test results of the ceramic capacitor prepared by the slurry of Example 1 are shown in FIG. Figure 1 It can be seen that after sintering, the slurry surface is dense and the internal and external electrodes are well connected; Figure 2 The following are the test results of the terminal electrode density of ceramic capacitors made by sintering CX701 slurry in unhumidified nitrogen. Figure 2 It shows that the surface of the slurry is dense after sintering, but there are gaps at the connection between the inner and outer electrodes; Figure 3 The following are the test results of the terminal electrode density of ceramic capacitors made by sintering CF63 slurry in unhumidified nitrogen. Figure 3 It shows that the surface density of the slurry after sintering is general and there are some gaps at the connection between the inner and outer electrodes; Figure 4 The results of the terminal electrode density test of ceramic capacitors made by sintering imported slurry in unhumidified nitrogen are shown below. Figure 4 It can be seen that the density of the slurry after sintering is general, but the internal and external electrodes are well connected.

[0060] Figure 5 The insulation resistance test results of the ceramic capacitors made from the slurry of Example 1 and the imported slurry sintered in unhumidified nitrogen are shown in FIG. Figure 5 It can be seen that the slurry of Example 1 has more stable high-temperature insulation performance. However, the ceramic capacitor obtained by the imported slurry expands or contracts rapidly when subjected to a 275°C thermal shock, and is prone to cracks or internal electrode breakage, poor contact between internal and external electrodes, and other problems, showing a decrease in resistance.

[0061] As can be seen from Table 3, in Comparative Example 1, due to the poor content of glass powder, the nickel permeability increased, the heat resistance of the capacitor decreased, and the density decreased; in Comparative Example 2, the content of organic binder was not good, and the heat resistance of the capacitor decreased; in Comparative Example 3, the amount of copper powder added was too high, the density of the slurry after sintering decreased, and the high-temperature stability became worse; in Comparative Examples 4-6, due to the change in the content of glass powder components, the density of the slurry decreased and the nickel permeability increased significantly; in Comparative Example 7, an equal amount of GeO2 was added to SiO2 with the same effect, in Comparative Example 8, an equal amount of SrO and K2O was added to CaO with the same effect, and in Comparative Example 9, an equal amount of TiO2 was added to Al2O3 with the same effect. Due to the reduction in the types of glass powder, the high-temperature insulation performance of the capacitor was weakened; in Comparative Example 10, the ceramic capacitor was prepared by sintering in nitrogen without humidification treatment. Compared with the capacitor treated with humidified nitrogen, the overall performance is reduced. At the same time, compared with commercially available CX701, CF63 and imported slurries, the slurry of the present invention can be sintered at a lower temperature, so that the sintered ceramic capacitor has better performance, lower internal stress and more stable high-temperature insulation performance.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A copper terminal electrode slurry, characterized in that: Calculated by mass percentage, it includes the following components: 65% to 70% copper powder, 8% to 15% glass powder, 17% to 27% organic binder; The glass powder is composed of the following components in percentage by mass: 20% to 35% BaO, 15% to 22% B2O3, 20% to 30% ZnO, 7% to 13% Al2O3, 6% to 10% CaO, 6% to 12% SiO2, 1% to 5% GeO2, 0.05% to 0.3% SrO, 0.05% to 0.5% TiO2, 0.05% to 0.3% K2O, 1% to 5% Li2O, and 1% to 5% La2O3.

2. The copper terminal electrode slurry according to claim 1, characterized in that: The particle size of the copper powder is 0.5 μm to 3.0 μm.

3. The copper terminal electrode slurry according to claim 1, characterized in that: The organic adhesive includes an organic solvent, an organic resin and an organic additive; the organic solvent is at least one of alcohols, esters, aromatic hydrocarbons and ether solvents; the organic resin is a polymer of acrylic resin and PVB resin and / or a polymer of acrylic resin and ethyl cellulose; the organic additive includes at least one of a dispersant, a leveling agent, a defoaming agent and a stabilizer.

4. The method for preparing the copper terminal electrode slurry according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly mixing the copper powder, glass powder and organic binder, and grinding the mixture to a fineness of ≤6.0 μm to obtain the copper terminal electrode slurry.

5. The method for preparing the copper terminal electrode slurry according to claim 4, characterized in that: Satisfy at least one of the following: (1) The preparation method of the organic binder is as follows: fully dissolving an organic auxiliary agent and an organic resin in an organic solvent at 80° C. to 95° C.; (2) The preparation method of the glass powder is as follows: the components of the glass powder are mixed uniformly by ball milling, melted at 1300° C. to 1400° C., quenched, and crushed to an average particle size of 2 μm to 3 μm, and sieved to obtain the glass powder.

6. Use of the copper terminal electrode slurry according to any one of claims 1 to 3 in ceramic capacitors.

7. A method for preparing a ceramic capacitor, comprising the steps of mixing slurry, making dielectric diaphragms, alternately overprinting inner electrodes and dielectric layers, laminating, cutting, debinding, sintering, capping electrodes, burning terminals, nickel plating and tin plating, characterized in that: The method for sintering the ends is as follows: applying the copper end electrode slurry described in any one of claims 1 to 3 to both ends of the ceramic core of the ceramic capacitor, drying, and sintering in an inactive gas; the sintering includes sintering in a low-temperature zone and sintering in a high-temperature zone, and the inactive gas sintered in the low-temperature zone is humidified; the sintering in the low-temperature zone is carried out at a constant temperature of 460°C to 470°C for at least 7 minutes, and the sintering in the high-temperature zone is carried out at a temperature of 740°C to 770°C for 5 minutes to 10 minutes.

8. The method for preparing a ceramic capacitor according to claim 7, characterized in that: The oxygen content in the inert gas during the low temperature zone sintering is 0 to 200 ppm.

9. A ceramic capacitor made by the method for making a ceramic capacitor according to any one of claims 7 to 8.